ANALISIS KINERJA KEUANGAN PERBANKAN SYARIAH DI INDONESIA SEBELUM DAN SELAMA MASA PANDEMI COVID-19 - Rosita Putri Kirana; Galuh, Ajeng Kartika (Journal of Development Economic and Social Studies, 2023)
The purpose of this study was to analyse the performance of Islamic financial banking in Indonesia both before and during the Covid-19 pandemic as measured using CAR, ROA, NPF, BPO, NOM and FDR ratios. The data analysis used is included in the quantitative type. The data source used in the form of monthly Islamic banking statistics for 2017-2022. The population in this study are all Islamic banks in Indonesia that are registered with the Financial Services Authority (OJK) for the 2017-2022 period. The analytical method test showed that there were significant differences in the CAR, ROA, NPF, BOPO, NOM and FDR ratios before and during the Covid-19 pandemic in Indonesia.